2022
DOI: 10.1108/ijopm-06-2021-0387
|View full text |Cite
|
Sign up to set email alerts
|

How can suppliers increase their buyers’ CSR engagement: the role of internal and relational factors

Abstract: PurposeBuyer engagement proves important supports for suppliers' corporate social responsibility (CSR); however, little is known about whether and how buyer CSR engagement can be actively searched for by a supplier and what activities and policies of suppliers could enhance buyer CSR engagement. From the perspective of resource dependence theory, this study aims to explore how suppliers seek to achieve buyers' CSR engagement.Design/methodology/approachThe proposed model and hypotheses were tested by structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 112 publications
(131 reference statements)
1
15
0
Order By: Relevance
“…Our results support this because although we found industrylevel GHG intensity to be a significant determinant of supply chain engagement (supporting H3), business strategies (H1) and political activity (H2) were considerably stronger determinants. We found that GHG intensity also increased customer engagement, thereby supporting a recent Peng et al (2022) study that indicated instrumental motives affect customer engagement. Consequently, both supplier and customer engagement in the disclosure procedure help reduce emissions' total impact in supply chains--not just supplier engagement, as Jira and Toffel (2013) and Luo et al (2012) also reported.…”
Section: Theoretical Implicationssupporting
confidence: 88%
See 4 more Smart Citations
“…Our results support this because although we found industrylevel GHG intensity to be a significant determinant of supply chain engagement (supporting H3), business strategies (H1) and political activity (H2) were considerably stronger determinants. We found that GHG intensity also increased customer engagement, thereby supporting a recent Peng et al (2022) study that indicated instrumental motives affect customer engagement. Consequently, both supplier and customer engagement in the disclosure procedure help reduce emissions' total impact in supply chains--not just supplier engagement, as Jira and Toffel (2013) and Luo et al (2012) also reported.…”
Section: Theoretical Implicationssupporting
confidence: 88%
“…Thus, investing in environmental practices is not beneficial for suppliers if their customers are not doing the same, and gains can be achieved only if these customers value their suppliers' efforts. It also has been found that suppliers can engage their customers and increase customers' dependency in business through instrumental motives and international environmental policies (Peng et al, 2022). Thus, from a supplier perspective, engaging with customers in carbon management is essential and can improve business.…”
Section: Customer Engagementmentioning
confidence: 99%
See 3 more Smart Citations